(untitled) (Prostor, 2024)
The urban fabric of cities is in constant flux. This paper is focused on two areas of former “Fotokemika” industrial complexes for production of photographic materials, located in Zagreb and Samobor. Complexes are analyzed based on previous studies, archive material and field research. The results compare their urban transformations in contemporary urban context with new uses. The aim is to detect urban, micro-urban and architectural characteristics in order to understand how they change through time within each city by comparing the initial contexts in the first half of the 20th century and contemporary situations followed in the period between 2020 and 2024.